Blood Glucose Level Lowering Effect Of Alkaline Reduced Water (ARW) In Streptozotocin-Induced Diabetic Rats - Poppy Diah Palupi; Metrikana Novembrina; Buanasari Buanasari; Fita Rahmawati; Tri Murti Andayani (Majalah Farmaseutik, 2020)
Alkaline Reduced Water (ARW) is beneficial to prevent oxidative stress disease such as diabetes. The aim of the study is to determine the effect of ARW on reducing blood glucose level in diabetic rats induced streptozotocin. Fifteen male Wistar rats were divided into 3 groups. Group 1 (normal) nondiabetic rats, group 2 diabetic rats (negative control) received single intraperitoneal of streptozotocin (65mg/kg), group 3 was diabetic rats treated with ARW 20 mL/kg/day, orally for 28 days. Blood samples were collected through retro-orbital method before and after the experiment. Measured parameter were body weight and blood glucose concentration. Data were analyzed using one-way analysis of variance test followed by Dunnet multiple comparisons post hoc test.  Administration of ARW for 28 days resulted in significant (p< 0.05) lowering of blood glucose. In conclusion, the results show that ARW can lower elevated blood glucose against streptozotocin-induced diabetes in rats.